Dampak Pemenuhan Cakupan Imunisasi di Masa Pandemi Covid-19 - Riski Muhammad Akbar Kaharuddin; Henny Permatasari; Poppy Fitriyani (STIKes Hang Tuah Pekanbaru, 2022)
Introduction: Indonesia reported the first case of COVID-19, the coverage of routine immunization to prevent diseases in children such as measles, rubella, and diphtheria is decreasing. For example, diphtheria, pertussis and tetanus (DPT3) and measles and rubella (MR1) immunization coverage rates were reduced by more than 35% in May 2020 compared to the same time period in the previous year. Objective: To analyze the fulfillment of immunization coverage during the Covid-19 pandemic. Method: The method used is a systematic review taken from various sources from several online databases at the University of Indonesia library, including Pro quest, Science Direct, Scopus, and Emerald Insight, literature searches using keywords by determining inclusion and exclusion criteria. Results: From the online database search results obtained, 10 journals were taken for analysis, the results of information about the impact of immunization coverage on children during the COVID-19 pandemic, and conducted an analysis of the published literature so that the impact of decreasing immunization coverage during the COVID-19 pandemic occurred thoroughly in various countries. This is due to national-scale restrictions in each affected country. Conclusion: Based on a systematic review of articles containing information about the impact of immunization coverage on children during the COVID-19 pandemic, and synthesizing the published literature so that the impact of decreasing immunization coverage during the COVID-19 pandemic occurred in various countries.